0615 Pitolisant in Combination With Other Medications for the Management of Narcolepsy. (12th April 2019) - Doghramji, Karl; Davis, Craig W; Patroneva, Albena; Schwartz, Jean-Charles; Scart-Grès, Catherine; Robert, Philippe; Wanaski, Stephen P; Krystal, Andrew D
Abstract: Introduction: Current standard of care in narcolepsy often involves polypharmacy. To characterize potential interactions of pitolisant with other narcolepsy medications, findings from a drug-drug interaction study and a phase 3 clinical study were evaluated. Methods: An open-label, crossover study, conducted in 16 healthy males, evaluated pharmacokinetic (PK) interactions of pitolisant (35.6 mg, single-dose) with sodium oxybate (4.5 g, divided-dose) and modafinil (200 mg/d for 22 days). In a long-term, open-label, phase 3 study (Month 12 completers, n=68), analyses of efficacy and adverse events included subgroups of patients with narcolepsy taking pitolisant alone (PIT), with psychostimulants (PIT+STIM), with anticataplectics (PIT+AC), and with psychostimulants and anticataplectics (PIT+STIM+AC). Results: Administration of pitolisant the morning after nighttime sodium oxybate did not affect pitolisant Cmax but slightly reduced AUC (≤14%) relative to pitolisant alone. Pitolisant did not affect sodium oxybate Cmax or AUC after the second sodium oxybate dose; sodium oxybate Cmax and AUC were slightly higher (15% and 12%, respectively) after the first sodium oxybate dose when used concomitantly with pitolisant. Coadministration of pitolisant with steady-state modafinil decreased pitolisant Cmax (15%) and AUC (19%); no effect of coadministered pitolisant was observed on modafinil PK. In the phase 3 study, mean change from baseline to Month 12 in Epworth Sleepiness Scale score was -4.7 for PIT (n=45), -3.2 for PIT+STIM (n=26), -3.6 for PIT+AC (n=14), and -4.0 for PIT+STIM+AC (n=13). Mean percentage change in daily number of generalized cataplexy attacks was -71.5% for PIT (n=21), -100% for PIT+STIM (n=11), -100% for PIT+AC (n=7), and -66% for PIT+STIM+AC (n=4). Conclusion: These data demonstrate that pitolisant has no effect on sodium oxybate or modafinil PK profile, and sodium oxybate has no clinically relevant effect on the PK profile of pitolisant. There is some decrease in pitolisant exposure when dosed concomitantly with modafinil; however, no dosage adjustment is required. Furthermore, in an open-label, real-world trial, pitolisant was effective both as monotherapy and in combination therapy with sodium oxybate, modafinil, and other common medications used in patients with narcolepsy. Support (If Any): Bioprojet Pharma and Harmony Biosciences, LLC.